(untitled) (Journal of Economic Research & Business Administration, 2016)
The article discusses the features of cost accounting in insurance organizations, including: the cost of conducting insurance business, such as the cost of conclusion, management and execution of insurance contracts, coinsurance and reinsurance, administrative and management expenses and general expenses, other expenses.